2016
DOI: 10.1111/jcpp.12614
|View full text |Cite
|
Sign up to set email alerts
|

Omega 3/6 fatty acids for reading in children: a randomized, double‐blind, placebo‐controlled trial in 9‐year‐old mainstream schoolchildren in Sweden

Abstract: Compared with placebo, 3 months of Omega 3/6 treatment improved reading ability - specifically the clinically relevant 'phonologic decoding time' and 'visual analysis time' - in mainstream schoolchildren. In particular, children with attention problems showed treatment benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…These findings indicate that LCPUFA supplementation has far-reaching effects, having additional benefits for learning. A recent 6-month 2-phase randomised trial with 154 children aged 9 and 10 years showed the omega-3/6 fatty acid supplementation improved reading ability in mainstream children and improved cognitive measures in children with attention problems, defined as those with ADHD symptom scores above the median [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that LCPUFA supplementation has far-reaching effects, having additional benefits for learning. A recent 6-month 2-phase randomised trial with 154 children aged 9 and 10 years showed the omega-3/6 fatty acid supplementation improved reading ability in mainstream children and improved cognitive measures in children with attention problems, defined as those with ADHD symptom scores above the median [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that a higher intake of n-3 PUFA supplements, especially DHA, may improve cognitive functions during the perinatal period and infancy, but not in childhood or adulthood [118,122,127,128]. Recently, Johnson et al [129], however, found that the increased intake of omega 3 and 6 fatty acids (DHA, EPA, and gamma-linolenic acid) for three months had a positive effect on prerequisites of reading and that the effects were particularly strong among those with a poorer attention.…”
Section: Nutrients Cognition and Academic Achievementmentioning
confidence: 99%
“…supplementation of FAs had weak if any association with cognitive performance in wellnourished children with no psychological or reading disabilities(12,24,39,40). It is possible that the intake of FAs(25) and the proportion of plasma FAs (41) among children in our study was adequate to support normal development of cognition(6,42).The other reason for no associations of dietary FAs with cognition in the present study may be that dietary FAs have different impacts on various cognitive domains.…”
mentioning
confidence: 53%
“…However, recent dietary (23) and supplementary (24) intervention studies suggest that increased intakes of omega-3 and omega-6 PUFAs and especially increased intakes of eicospentaenoic acid (EPA) and docosahexaenoic acid (DHA) are linked to improved cognitive skills in children 8-11 years of age. Nevertheless, there is limited knowledge on the associations of dietary intakes of other FAs than EPA and DHA with cognition.…”
Section: Introductionmentioning
confidence: 99%